A Mesh Grading Technique for Near-fault Seismic Wave Propagation in Large Velocity-contrast Viscoelastic Earth Media. Issue 3 (17th February 2022) - Zhong, Wei; Liu, Tielin
ABSTRACT: Seismic ground motions at a site are greatly affected by nearby many factors, such as strong heterogeneity, irregular interface, topographic relief, and large attenuation. To consider such factors, a simple triangular mesh grading technique is proposed for the efficient simulation of viscoelastic wave bidirectional propagation at irregular interface of large velocity-contrast earth media with rugged topography. The ground motions from finite-fault seismic source of a M w 5.2 hypothetical earthquake are simulated. The simulation results showed that the existence of soil basin and interlayer can impact greatly ground motions, and should be considered in studying ground motions.